2006
DOI: 10.1590/s0103-50532006000700030
|View full text |Cite
|
Sign up to set email alerts
|

Autoxidation of Ni(II) and Co(II) tetra, penta and hexaglycine complexes accelerated by oxy sulfur radicals

Abstract: A autoxidação dos complexos de Ni(II) e Co(II) com tetra, penta e hexaglicina, em meio de tampão borato, é acelerada por espécies de enxofre(IV) (H 2 SO 3 , HSO 3 -and SO 3 2-). A formação dos complexos de Ni(III) e Co(III) foi acompanhada espectrofotometricamente em 325 e 265 nm, respectivamente. Técnicas eletroquímicas também foram empregadas para caracterizar a geração destes complexos. A velocidade da reação de autoxidação aumenta com a concentração de S(IV) e é máxima em pH ≅ 8,5. O processo é autocatalít… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(43 reference statements)
1
2
0
Order By: Relevance
“…The N-dealkylation does not proceed to completion, suggesting another competing oxidation process, probably involving m-peroxo dicobalt complexes. Kinetics of autoxidation of Ni II and Co II complexes of tetrapenta-and hexa-glycine have been reported, 38 expanding on previous reports by the same authors. The decomposition of hexaaquacobalt(III) in aqueous perchloric acid has been reported.…”
Section: Redox Reactionssupporting
confidence: 63%
“…The N-dealkylation does not proceed to completion, suggesting another competing oxidation process, probably involving m-peroxo dicobalt complexes. Kinetics of autoxidation of Ni II and Co II complexes of tetrapenta-and hexa-glycine have been reported, 38 expanding on previous reports by the same authors. The decomposition of hexaaquacobalt(III) in aqueous perchloric acid has been reported.…”
Section: Redox Reactionssupporting
confidence: 63%
“…Our previous work 27 carried out in solutions containing each metal ion complex (Ni(II)/G n or Co(II)/G n ) in the presence of S(IV) and oxygen (at pH=9) showed that Ni(III)/G n formation is fast reaching a limit absorbance after 1s, followed by its decomposition via ligand oxidation. At the same experimental conditions, Co(III)/G n formation is much slower than Ni(III)/G n formation, after S(IV) consumption the Co(III)/G n formation is slow due to the oxidation of Co(II)/G n by the oxygen still remaining in solution.…”
Section: Initiation In the Absence Of Added Ni(ii) Or Co(ii)mentioning
confidence: 99%
“…In the case of Ni(II), several works have been reported in the literature (11,13,(16)(17)(18)(19). Currently, increasing interest in the formation of Ni(III) peptide complexes has been noticed because of the probable participation of these species in DNA damage processes (7).…”
Section: Introductionmentioning
confidence: 99%